The Effect of Promotion of Vessel Crew Vacancies on the Process of Changing Ship Crews at PT Jasindo Duta Segara - Sudiono Sudiono; Desamen Simatupang; Rosmayana Rosmayana; Ahmed Syah Rizan (Dinasti Publisher, 2022)
Crew Manning Agency is a division that only takes care of crew for ship owners overseas. PT. Jasindo Duta Segara uses International Safety Management (ISM) which aims to be the